2019
DOI: 10.3389/fvets.2019.00348
|View full text |Cite
|
Sign up to set email alerts
|

Endodontic Microbiome of Fractured Non-vital Teeth in Dogs Determined by 16S rRNA Gene Sequencing

Abstract: Dental fractures resulting in pulp exposure will lead to an endodontic infection with microbes from the oral cavity. However, data on the endodontic microbial composition in veterinary dentistry is lacking. The aim of this study was to examine the microbiome of naturally occurring primary endodontic infections in client-owned dogs. The endodontic microbiome of 10 non-vital teeth with exposed pulp cavities was assessed using a 16S rRNA gene sequencing approach. The results were compared to the microbiome of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Endodontic infections are the most frequent clinical lesions in the oral cavity, resulting in pain, swelling, pulpitis or apical periodontitis, and even root resorption. It was demonstrated that pathogenic microorganisms introduced by caries-induced breaches, dental surgical procedures, or trauma-induced cracks and fractures, led to the occurrence of endodontic infections. Particularly, biofilm-mediated infections play a critical role in the development of persistent endodontic infections (PEIs). As reported, Enterococcus faecalis (E. faecalis) has been found to be more prevalent in PEIs than other bacteria .…”
Section: Introductionmentioning
confidence: 99%
“…Endodontic infections are the most frequent clinical lesions in the oral cavity, resulting in pain, swelling, pulpitis or apical periodontitis, and even root resorption. It was demonstrated that pathogenic microorganisms introduced by caries-induced breaches, dental surgical procedures, or trauma-induced cracks and fractures, led to the occurrence of endodontic infections. Particularly, biofilm-mediated infections play a critical role in the development of persistent endodontic infections (PEIs). As reported, Enterococcus faecalis (E. faecalis) has been found to be more prevalent in PEIs than other bacteria .…”
Section: Introductionmentioning
confidence: 99%
“…The microbiome of the diseased endodontic system was found to have a comparable abundance of the same microorganisms as healthy subgingival plaque. Bacteroides and Snowella were the most abundant genera in the endodontic samples, while Porphyromonas and Fusobacterium were significantly more abundant in subgingival plaque (Rodrigues et al, 2019). An altered oral microbiome could have an impact on neonatal outcomes, since pregnant women and women with periodontal disease having higher levels of pathogenic bacteria in the mouth had an increased chance of negative neonatal and maternal outcomes.…”
Section: Oral Microbiotamentioning
confidence: 93%
“…Metagenomic studies are great for providing information about the healthy oral, intestinal, vaginal and placental microbiome. However, detection of bacterial DNA from the amnion and meconium by PCR does not necessarily mean that culturable bacteria are present in these fetal samples (Rodrigues et al, 2019). Studies in humans and livestock have shown that prenatal transmission of microbes to the fetus is possible, but there is no direct evidence of bacterial transmission in utero.…”
Section: Perspectivesmentioning
confidence: 99%